Responses of Human Neonates to Highly Diluted Odorants from Sweat - Loos, Helene; Doucet, Sèbastien; Vedrines, Fanny; Sharapa, Constanze; Soussignan, Robert; Durand, Karine; Sagot, Paul; Büttner, Andrea; Schaal, Benoist (Journal of Chemical Ecology, 2017)
Conjugated forms of odorants contributing to sweat odor occur not only in human sweat but also in amniotic fluid, colostrum, and milk. However, it is unclear whether the released odorants are detected and hedonically discriminated by human newborns. To investigate this issue, we administered highly diluted solutions of (R)/(S)-3-methyl-3-sulfanylhexan-1-ol (MSH), (R)/(S)-3-sulfanylhexan-1-ol (SH), (E)/(Z)-3-methylhex-2-enoic acid (3M2H), and (R)/(S)-3-hydroxy-3-methylhexanoic acid (HMHA) to 3-d-old infants while their respiratory rate and oro-facial movements were recorded. Adult sensitivity to these odorants was assessed via triangle tests. Whereas no neonatal stimulus-specific response was found for respiratory rate, oro-facial reactivity indicated orthonasal detection of MSH and SH by male neonates, and of HMHA by the whole group of neonates. Dependent on the dilution of odorants, newborns evinced neutral responses or longer negative oro-facial expressions compared with the reference stimuli. Finally, newborns appeared to be more sensitive to the target odorants than did adults.
Keywords: Olfaction; Human newborn; 3-methyl-2-hexenoic acid; 3-hydroxy-3-methylhexanoic acid; 3-sulfanyl-1-hexanol; 3-methyl-3-sulfanylhexan-1-ol